The Medieval Hebrew Encyclopedias of Science and Philosophy
XI, 549 p.
Keywords: In January 1998 leading scholars from Europe, the United States, and Israel in the fields of medieval encyclopedias (Arabic, Latin and Hebrew) and medieval Jewish philosophy and science gathered together at Bar-Ilan University in Ramat-Gan, Israel, for an international conference on medieval Hebrew encyclopedias of science and philosophy. The primary purpose of the conference was to explore and define the structure, sources, nature, and characteristics of the medieval Hebrew encyclopedias of science and philosophy. This book, the first to devote itself to the medieval Hebrew encyclopedias of science and philosophy, contains revised versions of the papers that were prepared for this conference. This volume also includes an annotated translation of Moritz Steinschneider's groundbreaking discussion of this subject in his Die hebraeischen Übersetzungen. The Medieval Hebrew Encyclopedias of Science and Philosophy will be of particular interest to students of medieval philosophy and science, Jewish intellectual history, the history of ideas, and pre-modern Western encyclopedias.